Analisis Efektivitas Mesin VL. GSK 6039 Pada Proses Pembubutan Wheelhub Front Menggunakan Metode OEE dan FMEA di PT. XYZ - Ilham Dwi Pranajaya; Akhmad Wasiur Rizqi (Universitas Islam Raden Rahmat, Malang, 2025)
PT. XYZ is a company in the field of spare parts manufacturing services such as wheelhub fronts. The machine used in the machining process is the VL. GSK 6039 machine which results in defects such as visual defects and oversize. This study was conducted to evaluate machine performance and defect factors using OEE and FMEA methods. OEE analysis showed a value of 38% below the international standard of 85%. In addition, 3 factors were found, namely humans, methods, and machines, from visual defects and oversize. Visual defects obtained RPN value 574 and oversize obtained RPN value 742. From these results, improvement suggestions are made, namely increased supervision, training, and rest hours for workers, guidance and improvement of SOP standards, increased machine maintenance and maintenance, and training in correct measuring instruments. In order to be implemented effectively, the company must form a special team of management representatives, technicians, and operators to oversee the implementation of improvements, periodic evaluations by comparing changes in OEE values before and after implementation, training every 2 weeks or once a month, placing a work area coordinator to ensure it is running properly, developing a more structured machine maintenance schedule, and implementing scheduled 60-30 minute breaks.